Pandangan Muslim Terhadap Sektor Fitness and Mind Body: Literature Study Approach Model - Sunarmo Sunarmo; Hanny Nurlatifah; Bambang Eko Samiono; Ani Asriyah; Sabda Ilahi Rizki; Nadiyah Afifah (ITB AAS INDONESIA Surakarta, 2021)
Healthy lifestyle is an inseparable thing for Indonesian people today, including generation X (baby boomers), Y (millennial) and Z. Concern for health indirectly affects the growth of the health sector, especially the fitness and mind sub sector. The dominance of Muslims around 87% in Indonesia is an interesting study for research because there are still not many studies on it. Literature research methods by collecting data and retrieving data from libraries, reading, taking notes, and processing research materials. The results of the research on the preferences of the Muslim community in Indonesia in choosing halal wellness, especially the fitness & mind body sub-sector according to the provisions of the DSN-MUI Number 108 of 2016 concerning Guidelines for Implementation of Tourism based on Sharia Principles such as room facilities, availability of places for equality, gender separation, dress code availability of halal food and drinks, etc. Keywords: Halal, Muslim consumers, literature study approach., fitness & mind body subsectors.